Satisfaction Level Analysis of the Library Visitor in Faculty of Science and Technology UIN Sunan Kalijaga - Pipit Pratiwi Rahayu; Mohammad Farhan Qudratullah (Kaunia: Integration and Interconnection Islam and Science, 2017)
This study aims to analyze the visitor satisfaction of the Faculty of Science and Technology Library by knowing whether there is a gap between the expectations and perceptions of visitors, measuring the level of service quality, and identifying things that need to be considered to improve service quality. The data was collected in November - December 2016 with systematic random sampling techniques obtained samples of 141 students respondents. The analysis tools used are gap analysis, paired data testing, and service quality formula. The results obtained there are gaps between expectations and perceptions of visitors in 5 (five) service dimensions which include: reliability, responsiveness, empathy, assurance, and tangibles, service quality levels is 80% with good category, and some things that need to be improved are availability of supporting facilities, room comfort, availability of catalogs, availability of signs in the library, and availability of collections.